Understanding the links between agriculture and health: Agriculture and nutrition linkages -- old lessons and new paradigms - Hawkes, Corinna; Ruel, Marie T. (International Food Policy Research Institute, 2006)
Agriculture is fundamental to achieving nutrition goals: it produces the food, energy, and nutrients essential for human health and well-being. Gains in food production have played a key role in feeding growing and malnourished populations. Yet they have not translated into a hunger-free world nor prevented the development of further nutritional challenges. Micronutrient deficiencies (for example, of vitamin A, iron, iodine, and zinc) are now recognized as being even more limiting for human growth, development, health, and productivity than energy deficits. Hunger among the poor also increasingly manifests itself through excessive consumption of energy-rich but nutrient-poor foods. The result is a double burden of undernutrition (deficiencies of energy, micronutrients, or both) and “overnutrition” (poor diet quality leading to obesity and other diet-related chronic illnesses).